Public–private interface in Brazilian education governance: Reflections from a subnational analysis - Hinke Dobrochinski Candido, Helena (Education Policy Analysis Archives, 2018)
This article investigates changes in the interference of the private sector in Brazilian public education, following the military dictatorship through today, focusing on evaluation policies that introduce data for education governance and results-based management. This research identifies changes related to educational policies and practices influenced by managerial models, showing the progressive disconnection of the public character from educational institutions. The political–educational context of the Brazilian state of Santa Catarina and its capital, Florianópolis, serves as the empirical case. Qualitative content analysis explores how ideas from the private sector have been integrated into Brazilian public education and how evaluation and the use of data according to the logic of that sector contribute to incorporating managerial practices into public education governance. Interviews with key actors in the field of education in Santa Catarina and Florianópolis reveal how the private sector influenced political developments in education. The analysis indicates that education governance in that context follows the principles of New Public Management, associated with public–private interactions, providing a specific type of rationality to the field of education.